Reframing History: New Historicism in Cinematic Critique of World War II Perspectives in 'The Fighter Pilot' (2013) and 'Saving Private Ryan' (1998) - Tano, Andreas; Simanjuntak, Immanuel Sheva (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This study aims at showing the biases of two contrast movies, ‘The Fighter Pilot’ on the Japanese side and ‘Saving Private Ryan’ on the American side in the context of New Historicism. Having the two movies analyzed, the New Historicism theory by Stephen Greenblatt (2011) was used to reveal the motives of both works. Two contextual aspects of the narratives were contrasted, ‘Idealized Image